Anger regulation in interpersonal contexts: Anger experience, aggressive behavior, and cardiovascular reactivity. (May 2019) - Beames, Joanne R.; O'Dean, Siobhan M.; Grisham, Jessica R.; Moulds, Michelle L.; Denson, Thomas F.
The ability to regulate anger facilitates harmonious interactions with strangers, colleagues, friends, and romantic partners. We review the influence of four emotion regulation strategies (i.e., cognitive reappraisal, suppression, angry rumination, and mindfulness) on subjective anger experience, cardiovascular reactivity, and aggressive behavior. All studies included a real or implied social interaction (e.g., with a fictitious participant). We included research on individual differences in emotion regulation as well as experiments that manipulated emotion regulation strategies. The evidence suggests that cognitive reappraisal and mindfulness can buffer anger-related responses in interpersonal contexts. Angry rumination perpetuates anger and aggression. The effects of suppression are mixed. Our review highlights the need for additional research into the extent to which emotion regulation strategies influence provoked anger and aggression in different interpersonal contexts.